Improving the shelf life of fresh cut kiwi using nanoemulsion coatings with antioxidant and antimicrobial agents. (June 2021) - Manzoor, Sabeena; Gull, Amir; Wani, Sajad Mohd; Ganaie, Tariq Ahmad; Masoodi, Farooq Ahmad; Bashir, Khalid; Malik, A.R.; Dar, B.N.
Abstract: The effect of nanoemulsion coatings with antioxidant and antimicrobial agents on the physicochemical, antioxidant properties and microbial stability of ready to eat fresh cut kiwi slices during storage at 5 ± 1 °C for 7 days was studied. Nanoemulsion coating formulations used were alginate 2% (w/w) and carboxymethylcellulose 2% (w/w) containing Tween 80 (2 mg), ascorbic acid 0.5% and vanillin 0.5 and 1.0%. Fresh cut kiwi slices were coated with nanoemulsion coatings, while the uncoated sample dipped in water served as control. Average drop diameter of the nanoemulsions was between 220 and 335 nm. Nanoemulsions had high negative ζ-potential value, significantly (P ≤ 0.05) lower viscosity and whiteness index values than coarse emulsions. During storage fresh cut kiwi fruit quality attributes especially weight loss, titratable acidity, total soluble solids, pH, ascorbic acid, firmness and microbial load were measured. Results confirmed that nanoemulsion coatings significantly delayed physiological weight loss 8–14%, decay percentage 3–59%, retained firmness 14.1–17.9 N, DPPH radical scavenging activity 53–59% and ascorbic acid content 73–79 mg 100 −1  g compared to control. Dispersion of several concentrations of the antimicrobial agent in a combination with emulsion coatings successfully slowed bacteria, yeast and mold growth during storage, thus leading to increased shelf life of fresh cut ready to eat kiwi fruit during storage. Graphical abstract: Image 1 Highlights: Nanoemulsion treatments enhanced the shelf life of fresh cut kiwi fruits. Coatings significantly minimized weight loss and decay percentages. Firmness and other quality parameters were retained using nanoemulsion coatings. Nanoemulsion coatings successfully reduced bacteria, yeast and mold counts.